INFLUENCE OF VARIOUS LAND USE SYSTEMS ON SELECTED SOIL PRODUCTIVITY PARAMETERS OF WETLAND SOILS. - Idris, S.; Lawal, H. M.; Maiyaki, M. M.; Mahmud, A. T.; Adamu, M. (FUDMA JOURNAL OF SCIENCES, 2023)
A scientific investigation was undertaken to compare productivity parameters of wetland soils as influenced by different land use systems. The study was conducted in Hadejia-Nguru wetlands, Nigeria. A total of 54 each of composite and core samples were collected across irrigated rice field, rainfed millet and natural fallow-land in three replicates, at 0-30 cm depth using stratified random sampling. Result showed that soil of fallow-land was statistically higher than soils of rice and millet land use systems in dry mean weight diameter (MWDd) (1.31) by 3.5 % and 4.4 %, wet mean weight diameter (MWDw) (0.349) by 5.4 % and 10.3 %, organic carbon (OC) (8.11 g/kg) by 5.9 % and 25.2 % and total nitrogen (TN) (1.28 g/kg) by 15.9 % and 40.81 % respectively. For saturated hydraulic conductivity, fallow-land recorded highest compared to millet and rice by 6.73 % and 20.18 % respectively. Rice land use had greater cation exchange capacity (CEC) than fallow-land and millet land use by 9.3 % and 11.8 % and sodium (Na+) by 62.3 % and 62.5 % respectively. Soil pH values obtained showed that rice land use had the least (pH 5.25), which could be due to leaching process. Fallow-land was inferred to be best in nutrient reserve and physical attributes. It’s therefore recommended that conservation agriculture be adopted in rice and millet land uses to replenish depleted nutrients and improve physical attribute of the soils. Use of heavy machineries in the two cultivated land uses should be minimized